(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2017)
Tourism is one of the important sectors in giving a good economic impact for the State of Kelantan. Gunung Stong State Park (GSSP) is one of them due to the presence of second highest waterfall in Southeast Asia, Jelawang Waterfall. This study is to identify the benefits received by local communities and to determine the role of GSSP in providing income from sustainable tourism. Results show that local communities receive benefits in term of road maintenance, exposure to tourists, improvement of infrastructure quality, enhancement of recreational activities and revenue potential. Result also indicates GSSP play roles in income from sustainable tourism and local communities have high awareness on the importance of GSSP. Entrepreneurship plays a crucial to helps and improves the quality of life of local communities.